Peran Baitul Maal Wa Tamwil (BMT) dalam Meningkatkan Kinerja Usaha Rumah Tangga di Purwokerto - Suyoto Suyoto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This study is titled The Role of Baitul Maal Wa Tamwil (BMT) in Improving Business Performance Scale Households in Purwokerto, it’s carried out in order to determine the role of BMT in improving business performance household scale, the potential of BMT in household-scale enterprises development, and the contribution BMT in household-scale enterprises development From the research result shows that BMT has a strategic role to improve the business performance scale household because the financing needs of TMB bridge between bussiness with financial institutions. BMT has a good potential for business development so that developing domestic scale becomes larger. BMT gives contribute the development of household scale so it can encourage economic growth, employment, and other follow-up impact